Panorama of the Municipal Sanitation Plan of Santo Antônio do Rio Abaixo, Minas Gerais (Research, Society and Development, 2019)
Basic sanitation contributes directly to the well-being and health of the population, as well as the preservation of the environment. Thus, this article aimed to analyze the municipal basic sanitation plan and the diagnosis of the pillars that compose the basic sanitation of the municipality of Santo Antônio do Rio Abaixo (MG). The methodology used was qualitative, based on the analysis of the municipal sanitation plan, prepared by the Caratinga Educational Foundation (FUNEC). It was verified that the municipality of Santo Antônio do Rio Abaixo has water catchment and distribution systems, which serves 47% of the total population of the municipality, however, there is no control of drinking water standards. In relation to the sanitary sewage system it was possible to notice that the effluents are not treated but dumped in natura in the Santo Antônio River. Despite the municipality does not have a landfill, a part of the waste is recycled, and the rest is incinerated or destined for the municipal garbage dump. As for the storn drain system, it was checked that this is inefficient, containing several areas with buildup of sediments. In general, it should be underlined that the implementation of the basic sanitation plan in the municipality is important to comply with Federal Law n° 11,445 / 2007, which aims to ensure the population access to potable water supply, sewage disposal, solids waste management and storn drain system, ensuring the preservation of the population’s physical and mental health, as well as the protection of natural resources.